Seafaring in the contemporary Pacific islands : studies in continuity and change - Feinberg, Richard (Northern Illinois University Press, 1995)
This collection of twelve original essays examines contemporary seafaring practices and the unique relationship of the islanders to the sea. The book adds a new dimension to present scholarship on the Pacific Islands by focusing on ordinary people and their attachment to the sea in the course of daily life rather than on the spectacular exploits of long-distance voyagers. Contributors to the volume examine islanders who depend on the sea for food and transportation, who paddle their canoes or fire up their outboard motors to transport copra to the local trader, whose songs and dances depict maritime themes, and for whom the sea provides a metaphor for all the vagaries of life. Geographical coverage of the book includes one Micronesian community (Enewetak), three Polynesian communities (Nukumanu, Sikaiana, and Rotuma), and four Melanesian ones (Marovo in the Western Solomons, Omarakana and Kaduwaga in the Trobriands, and Vanatinai in the Louisiade Archipelago). An essay on the Bugis of Indonesia points out the relevance of Island Southeast Asia to understanding seafaring in Oceania.